PERSPEKTIF PENGGUNA DOMPET DIGITAL: BENARKAH DOMPET DIGITAL TAK AMAN? - Sefita Indriati; Hilyah Kamilah; Tika Ayu Yulinda; Eka Sriutami; Aryan Danil Mirza BR (Goodwood Publishing, 2025)
The digitalization era marked by the Industrial Revolution 4.0 has brought significant changes in various aspects of life, including in the financial sector. The emergence of digital wallets as an alternative to conventional payment methods is increasingly popular. However, behind all these conveniences, there are concerns that continue to haunt users regarding the security of their personal data and financial transactions. This study aims to explore the perceptions of digital wallet users in Indonesia regarding security. Through an in-depth literature review and a survey of active users of various digital wallet platforms, this research seeks to identify key factors that influence users' level of confidence in the security of the digital wallets they use. The results showed a positive correlation between perceived security and intensity of digital wallet usage. Nonetheless, concerns about potential data security risks remain a key consideration for most respondents. Factors such as service provider reputation, ease of use of security features, and transparency in handling personal data are the main determinants of users' level of trust. In addition, the study also revealed a gap between users' perceptions and their knowledge of the security mechanisms implemented by digital wallet service providers.